2016
DOI: 10.1038/srep29673
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor and STAT1 cooperate downstream of Gas6/Mer to induce anti-inflammatory arginase 2 expression in macrophages

Abstract: Mer signaling increases the transcriptional activity of liver X receptor (LXR) to promote the resolution of acute sterile inflammation. Here, we aimed to understand the pathway downstream of Mer signaling after growth arrest-specific protein 6 (Gas6) treatment that leads to LXR expression and transcriptional activity in mouse bone-marrow derived macrophages (BMDM). Gas6-induced increases in LXRα and LXRβ and expression of their target genes were inhibited in BMDM from STAT1−/− mice or by the STAT1-specific inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…Consistent with the flow cytometry data, SIGN‐R1 and MARCO expression in the splenic MZ was restored to a certain extent in Mer −/− mice treated with GW3965 diet than in Mer −/− mice on a regular diet (Figure e). LXRs are known to promote anti‐inflammatory signaling pathways in immune cells . In accordance, when we challenged Mer −/− macrophages with ACs in the presence of LXR agonist GW3965, we found that the TNFα production by these macrophages was reduced by almost twofold (Figure f).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with the flow cytometry data, SIGN‐R1 and MARCO expression in the splenic MZ was restored to a certain extent in Mer −/− mice treated with GW3965 diet than in Mer −/− mice on a regular diet (Figure e). LXRs are known to promote anti‐inflammatory signaling pathways in immune cells . In accordance, when we challenged Mer −/− macrophages with ACs in the presence of LXR agonist GW3965, we found that the TNFα production by these macrophages was reduced by almost twofold (Figure f).…”
Section: Resultssupporting
confidence: 67%
“…Several recent reports have indicated the interdependence of Mer signaling and LXR transcriptional activity in macrophages. The activation of LXRs during AC clearance induces Mer expression, whereas Mer signaling in macrophages increases the anti‐inflammatory transcriptional activity of LXRs . Most importantly, LXRα is the only known transcriptional regulator of macrophage differentiation in the splenic marginal zone, where it is essential for the differentiation of SIGN‐R1 + MZMs and CD169 + MMMs .…”
Section: Resultsmentioning
confidence: 99%
“…This finding has been further supported by studies from other groups [23,24]. However, the anti-inflammatory function of Arg-II in macrophages is also described in the literature [25][26][27]. To our knowledge, the role of Arg-II in age-associated adipose tissue macrophage inflammation and the underlying molecular mechanisms are not clear.…”
Section: Introductionsupporting
confidence: 73%
“…Interestingly, the enhanced Arg-I levels in the aging adipose tissue under Arg-II deficiency are correlated with decreased age-associated inflammation, that is, macrophage accumulation and IL-6 levels in the adipose tissue, which could be due to the fact that Arg-I is upregulated in the M2-like macrophages which play an anti-inflammatory role [38][39][40][41][42]. In contrast to Arg-I, Arg-II is often associated with pro-inflammatory M1-like phenotype cells [18,41], although controversies are reported in the literature [18,[22][23][24][25][26][27]. The reasons for the controversies are not clear; it is most likely due to the different inflammation disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, overexpression of ABCA1 induces expression of the anti-inflammatory cytokine IL10, a marker of the M2 macrophage phenotype, via a protein kinase A-dependent pathway [98]. Activation of LXRs has also been shown to increase expression of arginase 1 and arginase 2, two additional markers of the M2 phenotype [102][103][104]. These studies support the hypothesis that LXRs function to counterinflammation and favor resolution of the inflammatory response.…”
Section: Macrophage Phenotypesupporting
confidence: 56%